Meningkatkan Kemandirian Siswa Dalam Pak Melalui Metode PBL Berbantuan LKPD Interaktif Materi Keberagaman Di SMAS ST.Maria Tanjungpinang - Vrisca Aderiani Siburian (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The independence of students at Santa Maria Tanjungpinang Catholic High School in responding to the problems they are facing has not been created and developed well so that student activity in the learning process has not been maximized. Students still have to be guided and accompanied throughout the learning process so that the initiative to seek information or learn independently has not developed well because they still depend on the teacher. This classroom action research was carried out with the aim of finding out the increase in student independence after implementing the problem based learning model assisted by interactive LKPD in understanding diversity material as the original reality of human life and striving for peace and national unity in Catholic religious lessons to perfect the implementation of Catholic religious education learning in improving results. learn from students and make students able to understand the material being taught well. This research is action research. This research took place at the Santa Maria Catholic High School in Tanjungpinang and was carried out in October and November 2023, with the research subjects being 20 class XII 2 students. This research consists of two cycles, namely Cycle I which begins with planning, acting, observing and reflecting. Based on the results of observations in the learning process that has been carried out in the classroom, there are still students who are less active in the learning process. The independence dimension reached 71.87%. During the post test, only 16 students passed, 4 students did not pass with an average score of 77.75. Thus, the research must be continued to the next stage (Cycle II). In cycle II, the independence dimension increased to 92.85% and 19 students graduated in the proficient and proficient category with an average score of 88. Based on the research results, there was an increase in student learning outcomes with the Problem Based Learning learning model assisted by interactive LKPD in cycle I the independence dimension was (71.87%) and in cycle II it was (92.85%). Meanwhile, the learning achievement results in cycle I were with an average score of 77.75 and increased in cycle II to 88. Thus, the PBL model assisted by interactive LKPD can increase student independence in PAK learning.